Deriving Effective Soil Water Retention Characteristics from Shallow Water Table Fluctuations in Peatlands. Issue 10 (14th October 2016) - Dettmann, Ullrich; Bechtold, Michel
Abstract : Core Ideas: This is a new approach for determining in situ peat soil water retention characteristics. It only requires data on water table changes, precipitation, and microrelief. Water table rises are used to invert for water retention parameters. Applicability is demonstrated for field data from a peatland. This approach should be applicable to other shallow groundwater systems. We have developed a novel and simple approach that can be used to derive effective in situ soil water retention characteristics from field monitoring time series in peatlands. The simplicity of the approach is given by the very limited data requirements, which comprise only precipitation, water table, and, if relevant, microrelief data. Our approach is built on two main assumptions: (i) for shallow groundwater systems, the soil moisture profile is always close to hydrostatic equilibrium; and (ii) during short time periods of high precipitation, the water storage change due to lateral fluxes is small compared with the precipitation input. Given these assumptions, the height of a water table rise due to a precipitation event mainly depends on the soil water retention characteristics, the precipitation amount, the initial water table depth, and, if present, the microrelief. In this study, this dependency was used to determine the effective van Genuchten parameters by Bayesian inversion assuming a uniform soil profile. We applied our concept to field data from a peatland with microrelief. Results indicated that observations of water table rises caused by precipitation events can contain sufficient information to constrain the soil water retention characteristics around monitoring wells in peatlands to plausible ranges. In principle, the approach should also be applicable to other shallow groundwater systems. Application limits and potential systematic errors are discussed.